Human bitter perception correlates with bitter receptor messenger RNA expression in taste cells - Lipchock, Sarah V; Mennella, Julie A; Spielman, Andrew I; Reed, Danielle R (The American journal of clinical nutrition, 2013)
Background: Alleles of the receptor gene TAS2R38 are responsible in part for the variation in bitter taste perception of 6-n-propylthiouracil (PROP) and structurally similar compounds (eg, glucosinolates in cruciferous vegetables). At low concentrations, people with the PAV (“taster” amino acid sequence) form of TAS2R38 perceive these bitter compounds, whereas most with the AVI (“nontaster” amino acid sequence) form do not; heterozygotes (PAV/AVI) show the widest range of bitter perception.Objectives: The objectives were to examine individual differences in expression of PAV-TAS2R38 messenger RNA (mRNA) among heterozygotes, to test the hypotheses that the abundance of allele-specific gene expression accounts for the variation in human bitter taste perception, and to relate to dietary intake of bitter-tasting beverages and foods.Design: Heterozygous individuals (n = 22) provided psychophysical evaluation of the bitterness of PROP, glucosinolate-containing broccoli juice, non–glucosinolate-containing carrot juice, and several bitter non-TAS2R38 ligands as well as dietary recalls. Fungiform taste papillae were examined for allele-specific TAS2R38 expression by using quantitative polymerase chain reaction.Results: PAV-TAS2R38 mRNA expression was measured in 18 of 22 heterozygous subjects. Relative expression varied widely and positively correlated with ratings of bitterness intensity of PROP (P = 0.007) and broccoli juice (P = 0.004) but not of the control solutions carrot juice (P = 0.26), NaCl (P = 0.68), caffeine (P = 0.24), or urea (P = 0.47). Expression amounts were related to self-reported recent and habitual caffeine intake (P = 0.060, P = 0.005); vegetable intake was too low to analyze.Conclusions: We provide evidence that PAV-TAS2R38 expression amount correlates with individual differences in bitter sensory perception and diet. The nature of this correlation calls for additional research on the molecular mechanisms associated with some individual differences in taste perception and food intake. The trial was registered at clinicaltrials.gov as NCT01399944.